Coagulation activation after discontinuation of VTE treatment with different oral anticoagulants and impact on 12-month clinical outcomes. Issue 2 (August 2015) - Beyer-Westendorf, Jan; Gehrisch, Siegmund; Stange, Thoralf; Tittl, Luise; Siegert, Gabriele; Weiss, Norbert
Abstract: Increasing D-dimer (DD) levels after discontinuation of vitamin K antagonist (VKA) therapy indicate an increased risk of recurrence of venous thromboembolism (VTE). However, after discontinuation ofd irect-actingn on-VKAo rala ntic oagulants (DOACs or NOACs) the extent of coagulation activation and its clinical impact is unknown. Blood samples were collected from consenting patients with proximal VTE at the end of anticoagulation treatment with apixaban (n = 37), dabigatran (n = 17), rivaroxaban (n = 9) or VKA (n = 184) and 4 weeks later. DD, prothrombin fragments F1 + 2 (F1 + 2) and thrombin–antithrombin complexes (TAT) were measured. All patients underwent follow-up at 12 months to establish recurrent VTE or death from any cause. Irrespective of the treatment, DD and F1 + 2 but not TAT demonstrated a similar increase between baseline and week 4. At 12 months, 18 patients (7.3%) had recurrent VTE and two (0.8%) had died. For all patients and subgroups of VKA and DOAC, positive likelihood ratios were numerically higher for baseline values but only TAT values at 4 weeks were found to be related to a small increase of outcome event likelihood (2.6; 95%CI 1.23-5.50), which was driven by VKA patients (3.1; 95%CI 1.32-7.30) and not by DOAC patients (2.27; 95%CI 0.52-9.95). For all parameters, negative likelihood ratios were not predictive. In logistic regression analysis, only ΔTAT (optimal cut-off > 178% from baseline demonstrated a significant risk increase for VTE/death (odds ratio 3.76; 95% confidence interval 1.46-9.68; p = 0.006). In conclusion, the concept of testing coagulation activation parameters may also be transferred to VTE patients at the end of DOAC therapy. For patients with an increase of TAT levels within 4 weeks after treatment discontinuation (> 178% from baseline) is associated with an increased risk for VTE recurrence or death at 12 months. Highlights: Changes of d-dimer, F1 + 2 and TAT are similar after cessation of VKA or NOAC therapy The concept to test coagulation activation at the end of VKA may be translated to NOAC patients increased d-dimer at baseline indicated risk of VTE recurrence or death (PLR 3.6) increased TAT values > 178% from baseline also indicated risk of VTE recurrence or death (PLR 2.6) in logistic regression, increase of TAT > 178% had a 3.8fold risk for recurrent VTE or death at 12 months